Should trainees be the ‘eyes and the ears’ of both good and bad practice in hospitals? - Sarfo-Annin, Jason Kwasi (Future Hosp J, 2015)
A strong voice is critical for junior doctors to report witnessed poor care delivery. Current incident reporting systems foster a sense of vulnerability and under-reporting of events. Provision of adequate incident report feedback and dedicated time to undertake audit and quality improvement projects are required to facilitate discussion and learning from errors that take place in the workplace. A independent whistleblowing centre specific to healthcare is required to reduce the likelihood of future inquiries into poor patient care.